DIGITAL TRANSFORMATION OF BANKS BASED ON THE DEVELOPMENT AND APPLICATION OF A DIGITAL STRATEGY (Conferencea, 2022)
The digital transformation of banks requires an integrated approach based on the development and application of a digital strategy. Digital transformation covers all aspects of financial and credit activities, including bank management mechanisms, therefore, the digital transformation of the banking sector should be coordinated with other development strategies in order to develop solutions that contribute to maximum efficiency. The digital strategy should be aimed at solving four main tasks: the introduction of digital technologies, the transformation of the process formation of the cost of services, the financial aspect of digitalization, as well as a change in the organizational structure.